2008
DOI: 10.1590/s0074-02762008000200010
|View full text |Cite
|
Sign up to set email alerts
|

IgG and IgG2 antibodies from cattle naturally infected with Anaplasma marginale recognize the recombinant vaccine candidate antigens VirB9, VirB10, and elongation factor-Tu

Abstract: Anaplasma marginale is an important vector-borne rickettsia of ruminants in tropical and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
3
19
0
2
Order By: Relevance
“…In comparison to the genes of the membrane proteins investigated in the present study, EF-Tu takes on significance as a possible candidate vaccine antigen, as it exhibits the highest percent homology among the predicted amino acid sequences in the isolates analyzed and is considered a highly conserved gene. This finding corroborates a study carried out by Araújo et al (2008), who report the conservation of this gene. Moreover, it is capable of stimulating the proliferative response in T lymphocytes, as reported by Lopez et al (2008).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In comparison to the genes of the membrane proteins investigated in the present study, EF-Tu takes on significance as a possible candidate vaccine antigen, as it exhibits the highest percent homology among the predicted amino acid sequences in the isolates analyzed and is considered a highly conserved gene. This finding corroborates a study carried out by Araújo et al (2008), who report the conservation of this gene. Moreover, it is capable of stimulating the proliferative response in T lymphocytes, as reported by Lopez et al (2008).…”
Section: Discussionsupporting
confidence: 93%
“…Ramos et al (2007) assessed the transcription pattern of several membrane proteins' genes in A. marginale, including EF-Tu, which, after analysis, was suggested to be a membrane-associated protein (Lopez et al 2005). Araújo et al (2008) and Lopez et al (2008) expressed EF-Tu in E. coli and the recombinant protein was able to induce a proliferative response in T lymphocytes and titers of IgG2 greater than those of IgG1, thereby demonstrating the desired capacity for immunostimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody specific for VirB9 in dogs infected with Ehrlichia canis was detected (24), and more recently, antibody specific for VirB9-2 and VirB10 was detected in cattle experimentally or naturally infected with A. marginale in Brazil (4,73). However, there is some evidence that type III secretion system (T3SS) proteins can induce protective immunity in several animal models with human pathogens (34,38,42,69).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it may play additional roles. It has recently been demonstrated that EF-Tu is released/secreted from bacterial cells and that it can modulate pathogen-host interactions (19)(20)(21)(22)(23)(24). However, the pathways by which EF-Tu protein might interfere with immune regulation in the host cell remain unknown.…”
Section: Discussionmentioning
confidence: 99%